The Readjusted Arabesque: Narrating Architecture in Literary Text, the Case of Kafka’s Bridge - Restrepo Restrepo, Esteban (Writingplace, 2021)
The architect is not the only artist who conceives architecture. As the most common spatial and material framework in which human life takes place, architecture also appears in other arts like painting, cinema, theatre and literature, where it is an unavoidable subject of conception and reflection. Among those arts, it is on the architectures that are present in literary texts that we will focus in this article. Unlike the architect, the writer conceives architecture with the technical conditions and the aesthetic particularities of the literary medium. Thus, the experience we make of literary architectures radically differs from the one we make of built architectures, which can be experienced first-hand and navigated at will. To appraise a literary architecture this contribution will use two analytical categories from Gérard Genette’s narratology, namely: the Voice or the situation of the narrator in relation to the story he tells, and its implications in the representation of architecture; and the Order or the sequences in which architecture is represented during the narration. We will use both categories to analyse Kafka’s short story The Bridge (Die Brücke).